S99 Pulmonary Rehabilitation in Interstitial Lung Disease – a prospective, observational study. (12th November 2015) - Sharp, C; McCabe, M; Hussain, MJ; Adamali, H; Smith, DL; Edwards, A; Millar, AB
Abstract : Background: Pulmonary rehabilitation (PR) is important in the management of interstitial lung disease (ILD), however it remains unclear how sustained the initial benefits in exercise capacity and quality of life are in this group of patients. An increasing number of ILD patients are participating in PR courses and it is vital that they be offered the most beneficial approach possible. Methods: We have analysed prospectively gathered data from a well characterised population of ILD participants with >24 months follow-up, from a well-established PR service. Participants completed incremental shuttle walk (ISWT) and chronic respiratory disease questionnaire (CRDQ) before PR, at course completion, 6 months and 12 months follow-up. These data were compared to establish changes over time compared to baseline. The ILD cohort was compared to a further group with chronic obstructive pulmonary disease (COPD). Semi-structured interviews were conducted with ILD participants to establish qualitative views on existing and possible future PR provision. Results: Data were available for 79 participants with ILD. PR gave initial improvements in ISWT (29.5 m (95% CI 13.7 to 45.2 m)) and CRDQ (11.6 (95% CI 8.5 to 14.7)), however these benefits were not sustained at 6 months (ISWT change 0.0 m (95% CI -23.2 to 23.2 m), CRDQ change 2.5 (95% CI -2.4 to 7.4)) and 12 months (ISWT change -0.7 m (95% CI -37.3 to 35.9 m), CRDQ change 4.0 (95% CI -2.2 to 10.2)). In contrast, the COPD group demonstrated more durable benefit in exercise capacity (ISWT change at 6 months 35.7 m, 95% CI 10.76 to 60.68, p < 0.01). A greater proportion of those who had continued with home exercise maintained an increase in walking distance above the MCID than those who had not (46.4% vs 10.5%, p = 0.01). Interview responses highlighted the value attached to PR by participants with ILD, but also suggested that this could be improved by increased course duration, ongoing supervised exercise following course completion and greater tailoring of content to those with ILD. Conclusions: PR as currently delivered gives initial benefits to participants with ILD, however these are not sustained. More tailored approaches to this group are needed to improve the sustainability of response to PR.